Implementasi Kegiatan Muhadharah dalam Meningkatkan Percaya Diri pada Dimensi Kreatif Siswa Kelas 4 di MIN 2 Bengkulu Tengah - Handayani, Anisa Apri Norma; Nurmartha, Doci; Sa’adah, Lutfiatu (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Education during the current implementation of the independent curriculum applies several principles in providing freedom and opportunities for students to increase their self- confidence by implementing the muhadharah program, especially on their talents and character through a project to strengthen the Pancasila learning profile. This creative dimension is fully supported by the school with extracurricular activities or extra hours. This journal aims to increase students’ self-confidence through muhadharah activities at MIN 2 Central Bengkulu. This type of research is qualitative research. So, the researcher chose to use descriptive qualitative research. The results of this research can be concluded, 1) Muhadharah activities include reading the Koran and prayers, remarks from the school principal, lectures, and other performances from the class on duty. 2) Obstacles in implementing muhadharah include: Sometimes some students lack motivation for muhadharah activities, such as they lack interest in learning one of the muhadharah programs. Students do not appreciate the activities of implementing muhadharah, which causes commotion and disorder during implementation.